A silicon-based PbSe quantum dot near-infrared photodetector with spectral selectivity. Issue 28 (13th July 2021) - Shi, Yuanlin; Wu, Zhiming; Dong, Xiang; Chen, Pengyu; Wang, Jinquan; Yang, Jun; Xiang, Zihao; Shen, Miao; Zhuang, Yaming; Gou, Jun; Wang, Jun; Jiang, Yadong
Abstract : A silicon-based photodetector with a selective response range is achieved by utilizing the tunable absorption peaks of colloidal quantum dots without additional complex optical structures. Abstract : Traditional photodetectors usually respond to photons larger than the bandgap of a photosensitive material. In contrast to traditional photodetectors for broad-spectrum detection, the currently reported PbS/PMMA/PbSe CQD silicon-based photodetectors can detect spectrally selective light sources. This is attributed to two layers with specific functions, a filter layer on top and a photosensitive layer in contact with the silicon channel. Each of the target sources of the device has a selectivity factor of more than 10 against non-target sources. The s-PD (selective photodetector) has three significant advantages: the ability to tunably adjust the detectable spectral range by easily adjusting the size of QDs. The second is using a new architecture to achieve a high-performance selective photodetector, and finally, the ease-of-integration with silicon. The above features enable the device to meet the needs of particular fields such as secure communication, surveillance, and infrared imaging.